Saline-alkali soil biological-mineral composite modifier prepared by utilizing industrial wastes and preparation method of saline-alkali soil biological-mineral composite modifier

By preparing a bio-mineral composite soil conditioner for saline-alkali land, utilizing alkali-activated steel slag, hydrothermal modified red mud, and modified biochar, combined with the MIP biomineralization reaction, the problems of short duration and weak deep soil improvement capacity of saline-alkali land conditioners were solved. This achieved long-term soil improvement and efficient resource utilization of industrial waste, significantly improving soil quality and crop yield.

CN121471924APending Publication Date: 2026-02-06INST OF GEOGRAPHICAL SCI & NATURAL RESOURCE RES CAS +1

Patent Information

Application Number
CN202511649863.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-12
Publication Date
2026-02-06

AI Technical Summary

Technical Problem

Existing saline-alkali land conditioners suffer from problems such as short duration of improvement effect, weak deep soil improvement capacity, insufficient utilization of industrial waste, high carbon emissions, and insufficient carbon neutrality benefits.

Method used

A bio-mineral composite amendment for saline-alkali land, prepared from industrial waste, is used to construct a three-phase synergistic system of minerals, organic matter, and organisms. It utilizes alkali-activated steel slag to provide an active calcium source, neutralizes red mud to form hydrated aluminosilicate gel, modifies biochar to enhance cation exchange capacity, and achieves long-term salt fixation through MIP biomineralization reaction.

Benefits of technology

It has achieved long-term improvement, full-layer improvement, carbon sequestration and carbon sink enhancement. The improvement effect lasts for 12-24 months. The physical and chemical properties of severely saline-alkali soil have been significantly improved, crop yield has increased by 40%-60%, and the resource utilization rate of industrial waste is >90%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_47
    Figure SMS_47
  • Figure SMS_50
    Figure SMS_50
  • Figure SMS_73
    Figure SMS_73
Patent Text Reader

Abstract

The invention belongs to the technical field of soil amendments, and particularly relates to a saline-alkali soil biological-mineral composite amendment prepared from industrial waste and a preparation method thereof. Alkali fusion activated steel slag provides a quick-acting active calcium source, hydrothermal modification neutralized red mud forms hydrated aluminosilicate gel solid sodium, modified biochar enhances cation exchange capacity, a composite functional bacterial agent drives MICP biomineralization reaction, a quick-acting-slow-release-storage three-stage gradient improvement system is established, and the quick-acting-slow-release-storage three-stage gradient improvement effect is achieved. According to the present invention, the effects of 0-50 cm soil profile full-layer improvement and 12-24 month continuous improvement are achieved, 90 d after the modifier is applied, the soil pH value of the severe saline-alkali soil is reduced to 7.8 from 10.1, the conductivity is reduced to 3.2 dS / m from 11.5 dS / m, the sodium adsorption ratio is reduced to 11 from 42, the crop yield increase amplitude reaches 40-60%, 15-25 kg of the modifier is fixed per ton, and the industrial waste resource utilization rate gt is achieved; 90%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of soil conditioner technology, specifically relating to a biological-mineral composite conditioner for saline-alkali land prepared using industrial waste and its preparation method. Background Technology

[0002] Saline-alkali land refers to land resources with excessively high salt content and severe alkalization, which restricts crop growth. my country has approximately 99.13 million hectares of saline-alkali land, accounting for more than 10% of the country's total arable land area, mainly distributed in the Songnen Plain in Northeast China, the North China Plain, the inland basins of Northwest China, and coastal areas. Saline-alkali land generally suffers from prominent problems such as high pH (typically >8.5), high soil electrical conductivity (exceeding 4 dS / m), high sodium adsorption ratio (SAR value >15), damaged soil aggregate structure, poor permeability, and low organic matter content, severely restricting the effective utilization of land resources and ensuring food security.

[0003] In the prior art, CN111303896A discloses a saline-alkali soil conditioner and a method for preparing a saline-alkali soil conditioner using phosphate mine tailings and low-rank coal. This technology obtains soluble calcium and magnesium by ripening phosphate mine tailings with concentrated sulfuric acid, activates humic acid by oxidizing and nitrifying low-rank coal with nitric acid, and then mixes the two, granulates them, and sprays them with a bacterial agent to prepare the conditioner.

[0004] However, existing technologies still have the following shortcomings: First, traditional soil amendments mainly rely on chemical neutralization and ion exchange mechanisms, lacking long-term salt fixation capabilities and having a short duration of improvement effects, typically lasting only 3-6 months, requiring frequent application and increasing costs. Second, existing technologies mostly employ single or binary component systems (such as mineral-organic or chemical-microbial composites), failing to fully utilize the synergistic effects of minerals, organic matter, and microorganisms, resulting in limited improvement effects on severely saline-alkali land (pH > 10, conductivity > 10 dS / m, sodium adsorption ratio > 40). Third, traditional soil amendments mainly act on the topsoil (0-20 cm), lacking sufficient ability to control salt migration in deeper soil layers (20-50 cm), making it difficult to achieve full-layer soil profile improvement. Fourth, existing technologies fail to effectively utilize the MMICP (microbially induced carbonate precipitation) biomineralization mechanism to achieve carbon fixation and long-term salt fixation, lacking ecological and environmental benefits in the context of carbon neutrality strategies. Fifth, research on the resource utilization of industrial wastes such as steel slag and red mud in the field of saline-alkali land improvement is relatively weak, and their advantages as active calcium sources and cementing properties have not been fully utilized.

[0005] Therefore, there is an urgent need to develop a new type of saline-alkali land conditioner and its preparation method that can achieve long-term improvement, full-layer improvement, carbon sequestration and resource utilization of waste. Summary of the Invention

[0006] The purpose of this invention is to address the shortcomings of existing technologies by providing a bio-mineral composite amendment for saline-alkali land prepared from industrial waste and its preparation method. This amendment breaks through the limitations of traditional single or binary components, innovatively constructing a mineral-organic-biological three-phase synergistic system. For the first time, the MIP biomineralization mechanism is applied to the field of saline-alkali land improvement. It achieves rapid ion exchange by providing an active calcium source through steel slag, neutralizes red mud to form hydrated aluminosilicate gel to fix sodium ions, enhances cation exchange capacity with modified biochar and serves as a microbial carrier, and drives microbial-induced carbonate precipitation reaction to achieve long-term salt fixation by using salt-alkali tolerant functional bacteria. This solves the technical problems of traditional amendments, such as short duration, weak deep improvement ability, high carbon emissions, and insufficient utilization of industrial waste.

[0007] To achieve the above objectives, the first aspect of the present invention provides a saline-alkali land biological-mineral composite amendment prepared from industrial waste, comprising the following components in parts by weight: 30-60 parts of alkali-activated steel slag powder 15-35 parts of hydrothermal modified and neutralized red mud 8-18 parts of alkaline functional group modified biochar. 2-6 parts of amino acid chelated trace elements 5-12 parts of compound functional microbial agent, Polyglutamic acid-encapsulated sustained-release urea, 10-20 parts. Sodium carboxymethyl cellulose binder, 2-5 parts.

[0008] The alkaline-activated steel slag powder is prepared by alkaline activation treatment of converter steel slag with sodium hydroxide solution at 120-160℃. It has a particle size of 80-200 mesh, a free calcium oxide content of 18%-32%, and an activity calcium index of 0.7-0.95. Alkaline activation significantly enhances the reactivity of silicate minerals and calcium-iron phases in the steel slag, enabling them to be rapidly released in saline-alkali soils. Ion exchange is performed to replace the adsorbed ions in the soil colloids. Simultaneously, through hydration reaction, hydrated calcium silicate gel and calcium hydroxide microcrystals are generated, which neutralize soil acid radicals and reduce soil pH and electrical conductivity.

[0009] The hydrothermally modified neutralized red mud is prepared by neutralizing Bayer process red mud with sulfuric acid, followed by hydrothermal modification at 150-190℃ and 0.5-1.5MPa pressure for 2-6 hours. It has a particle size of 100-300 mesh, an alumina content of 25%-40%, a well-developed mesoporous structure and active aluminosilicate phase, and a specific surface area of ​​40-85 m² / g. In saline-alkali soil environments, it can synergistically interact with steel slag hydration products to form a three-dimensional network of hydrated aluminosilicate gel structure, which is immobilized through a dual mechanism of physical encapsulation and chemical adsorption. This blocks the upward migration pathway of salt, while the iron and aluminum oxides in the modified red mud can serve as a carrier for microbial attachment, promoting the colonization of functional microbial communities.

[0010] The alkaline functional group modified biochar is produced from agricultural and forestry waste (straw, rice husks, or sawdust) through oxygen-limited pyrolysis at 500-650℃. It is then modified by ammonia impregnation to introduce alkaline functional groups such as amino and imino groups. The resulting biochar has a particle size of 40-120 mesh, a specific surface area of ​​150-350 m² / g, a cation exchange capacity of 50-120 cmol / kg, and a pH of 9-11. The introduction of numerous alkaline functional groups significantly enhances the biochar's cation exchange capacity and buffering capacity, enabling it to effectively adsorb and exchange ions from the soil. , It is isocationic, and its well-developed porous structure provides a habitat microenvironment for urease-producing bacteria and salt-tolerant microorganisms, promoting their survival and reproduction in the soil.

[0011] The amino acid chelated trace elements include the following components: amino acid chelated zinc 0.5%–1.5%, amino acid chelated iron 1%–3%, amino acid chelated manganese 0.3%–1%, and amino acid chelated boron 0.2%–0.8%. The amino acid chelation method improves the stability and bioavailability of trace elements in saline-alkali soil, improves crop nutrition, and promotes root development.

[0012] The compound functional microbial agent includes the following strains: Bacillus pasteurellis (urease-producing bacterium, viable count) (number / g), salt-tolerant phosphate-solubilizing bacteria (live count) (number / g), salt-alkali tolerant nitrogen-fixing bacteria (live count) (pcs / g), among which Bacillus pasteurellii is the core functional bacterium of the MIP biomineralization reaction, capable of secreting urease to catalyze the hydrolysis of urea to produce and In the release of steel slag Induced formation under certain conditions Precipitation will free and Mineralization into stable calcium carbonate crystals achieves long-term fixation. And sealed Salt-tolerant phosphate-solubilizing bacteria and nitrogen-fixing bacteria work synergistically to enhance soil nutrient availability and improve the rhizosphere microecological environment.

[0013] The polyglutamic acid-encapsulated slow-release urea uses γ-polyglutamic acid to encapsulate urea through electrostatic adsorption and physical encapsulation, forming composite particles with slow-release function. The urea nitrogen content is 35% to 45%, and it can be continuously released in the soil for 15 to 30 days. It serves as a substrate for the urease-catalyzed reaction of Bacillus pasteurellis to drive the MIP reaction, and can also provide nitrogen nutrition for crops, achieving dual benefits.

[0014] The sodium carboxymethyl cellulose binder has a degree of substitution of 0.6-0.9 and a viscosity of 300-800 mPa·s. As a natural polymer binder, it effectively binds the components together and forms a dense granular structure during the granulation process, thereby improving the mechanical strength and water resistance of the modifier and preventing rapid leaching of nutrients.

[0015] The beneficial effects of the biological-mineral composite amendment for saline-alkali land of this invention are: it provides a fast-acting active calcium source by alkali-activated steel slag, enabling rapid ion exchange and replacement. It has a rapid improvement effect; hydrothermal modification and neutralization of red mud form a hydrated aluminosilicate gel network, which is physically encapsulated and chemically fixed. It plays a role in slow-release and salt fixation; modified biochar provides a high specific surface area and strong cation exchange capacity, serving as an ion exchange reservoir and microbial carrier; composite functional bacterial agents drive the MICP biomineralization reaction, converting free... and the products of urea hydrolysis Mineralized into calcium carbonate crystals, it achieves long-term calcium and carbon fixation, forming a three-tiered gradient improvement system of rapid-release, slow-release, and storage, ensuring full-layer improvement of the 0-50cm soil profile and continuous improvement for 12-24 months, while achieving a resource utilization rate of over 90% for industrial waste. A fixed amount of 15-25 kg / t of amendment, with a comprehensive benefit of 40%-60% increase in crop yield.

[0016] Further, the preferred weight percentage of the alkali-fused activated steel slag powder is 40-50 parts, the preferred weight percentage of the hydrothermally modified neutralized red mud is 20-30 parts, the preferred weight percentage of the alkaline functional group modified biochar is 10-15 parts, the preferred weight percentage of the amino acid chelated trace elements is 3-5 parts, the preferred weight percentage of the composite functional microbial agent is 7-10 parts, the preferred weight percentage of the polyglutamic acid-encapsulated slow-release urea is 12-18 parts, and the preferred weight percentage of the sodium carboxymethyl cellulose binder is 3-4 parts.

[0017] Furthermore, the free calcium oxide content in the alkali-fused activated steel slag powder is preferably 22% to 28%, and the active calcium index is preferably 0.8 to 0.9.

[0018] Furthermore, the specific surface area of ​​the hydrothermally modified neutralized red mud is preferably 55-75 m² / g, and the alumina content is preferably 30%-36%.

[0019] Furthermore, the cation exchange capacity of the alkaline functional group modified biochar is preferably 70-100 cmol / kg, and the specific surface area is preferably 200-300 m² / g.

[0020] Furthermore, the preferred viable count of the *Bacillus pasteurellii* is... The optimal viable count of salt-tolerant phosphate-solubilizing bacteria is [number of bacteria / g]. The optimal viable count of salt-tolerant nitrogen-fixing bacteria is [number of bacteria / g]. per g.

[0021] The second aspect of this invention provides a method for preparing the saline-alkali land biological-mineral composite amendment prepared from industrial waste, comprising the following steps: Step 1: Preparation of Alkali-Activated Steel Slag Powder: Converter steel slag is pulverized to a particle size <5mm and mixed with a 20%–40% sodium hydroxide solution at a solid-liquid ratio of 1:2–1:4. The mixture is placed in a high-pressure reactor and reacted at 120–160℃ and 0.2–0.5MPa pressure for 2–5 hours. After cooling, the mixture is filtered and separated. The solid phase is washed with deionized water until the pH value reaches 8–9, dried at 105–110℃ for 4–8 hours, and then pulverized through an 80–200 mesh sieve to obtain alkali-activated steel slag powder. The alkali-activation process disrupts the stable silicate lattice structure in the steel slag, promotes the depolymerization of silicon-oxygen tetrahedra and the dissolution of the active calcium phase, significantly enhancing the hydration activity of the steel slag. Release rate.

[0022] Step 2, Preparation of hydrothermally modified and neutralized red mud: Bayer process red mud is mixed with a 10%–20% sulfuric acid solution at a solid-liquid ratio of 1:3–1:6, stirred and neutralized for 30–90 minutes until the pH value is 6–8, filtered and washed into the filtrate. For red mud with a concentration <500 mg / L, the neutralized red mud slurry is placed in a hydrothermal reactor and hydrothermally treated for 2–6 hours at 150–190℃ and 0.5–1.5 MPa pressure. After cooling, it is dried at 100–120℃ for 6–12 hours and then pulverized through a 100–300 mesh sieve to obtain hydrothermally modified neutralized red mud. This hydrothermal modification process promotes the recrystallization of the aluminosilicate phase and the development of the pore structure in the red mud, generating mesoporous materials with high specific surface area, thus enhancing its resistance to... Adsorption and fixation capacity.

[0023] Step 3, Preparation of alkaline functional group modified biochar: Agricultural and forestry waste (straw, rice husk or sawdust) is crushed to a particle size <3mm, heated to 500-650℃ in a tube furnace under nitrogen atmosphere at a heating rate of 5-10℃ / min, and pyrolyzed at a constant temperature for 1-3h. After cooling, primary biochar is obtained. The primary biochar is mixed with an ammonia solution with a mass fraction of 10%-25% at a solid-liquid ratio of 1:5-1:10, and impregnated at 60-80℃ for 4-8h. After filtration and washing until the pH value of the filtrate is 8-9, it is dried at 80-100℃ until the water content is <5%, and crushed through a 40-120 mesh sieve to obtain alkaline functional group modified biochar. The ammonia modification process introduces nitrogen-containing alkaline functional groups such as amino, imino, and amide groups on the surface of the biochar, which significantly improves the alkalinity, cation exchange capacity and buffering capacity of the biochar.

[0024] Step 4, Preparation of amino acid chelated trace elements: Zinc sulfate, ferrous sulfate, manganese sulfate, and boric acid are mixed and dissolved in deionized water at a mass ratio of 1:2:0.6:0.4 to prepare a mixed trace element solution with a total concentration of 50-100 g / L. Amino acids (glutamic acid, glycine, or compound amino acids) are added to make the molar ratio of amino acids to metal ions 2:1-3:1. The pH value is adjusted to 6-7, and the mixture is stirred and chelated at 60-70℃ for 2-4 hours. After cooling, it is spray-dried to obtain amino acid chelated trace element powder.

[0025] Step 5, Preparation of the compound functional bacterial agent: Inoculate *Bacillus pasteurellii*, salt-tolerant phosphate-solubilizing bacteria, and salt-tolerant nitrogen-fixing bacteria into their respective liquid culture media. Incubate at 30-35℃ with shaking at 150-200 rpm for 24-48 hours until the logarithmic growth phase. Collect the bacterial cells by centrifugation, resuspend them in sterile physiological saline, and mix the three bacterial solutions at a volume ratio of 2:1:1. Add sodium alginate (2%-4% by mass) as a protectant, and spray-dry or freeze-dry to prepare the bacterial powder. The total viable count is... The number of bacteria per gram is greater than 50 U / g, of which Bacillus pasteurellii has a urease activity >50 U / g of bacterial powder.

[0026] Step 6, Preparation of polyglutamic acid-encapsulated sustained-release urea: Urea particles are spray-coated with γ-polyglutamic acid aqueous solution (mass fraction of 8% to 15%) at a mass ratio of 1:0.1 to 1:0.3 in a fluidized bed coating machine. The spraying temperature is controlled at 50-70℃, the spraying pressure is 0.1-0.3MPa, and the coating time is 30-60min. Slow-release urea particles with a polyglutamic acid film on the surface are obtained and dried at 60℃ until the moisture content is <2%.

[0027] Step 7, Mixing and Granulation: Weigh out the alkali-fused activated steel slag powder, hydrothermally modified neutralized red mud, alkaline functional group modified biochar, amino acid chelated trace elements, and polyglutamic acid-encapsulated slow-release urea according to the formula ratio. Mix them in a high-speed mixer for 5-10 minutes. Add the compound functional bacterial agent and mix evenly. Dissolve sodium carboxymethyl cellulose in deionized water to prepare a binder solution with a mass fraction of 2%-5%. Granulate the material while spraying the binder solution in a disc granulator, controlling the material moisture content to 15%-25% and the granulation time to 15-30 minutes to obtain wet granules with a particle size of 2-5 mm. Dry the wet granules in a low-temperature fluidized bed dryer at 40-50℃ until the moisture content is <10%. Screen the finished granules to obtain a particle size of 2-4 mm, and package and seal them for storage.

[0028] Furthermore, in step one, the sodium hydroxide solution used for the alkali fusion activation reaction has a preferred mass fraction of 25%–35%, a preferred solid-liquid ratio of 1:2.5–1:3.5, a preferred reaction temperature of 130–150°C, and a preferred reaction time of 3–4 hours.

[0029] Furthermore, in step two, the mass fraction of the sulfuric acid solution used in the neutralization reaction is preferably 12%–18%, the solid-liquid ratio is preferably 1:4–1:5, the hydrothermal treatment temperature is preferably 160–180℃, and the hydrothermal treatment time is preferably 3–5 h.

[0030] Furthermore, in step three, the preferred pyrolysis temperature is 550-620℃, the preferred pyrolysis time is 1.5-2.5h, the preferred ammonia concentration for ammonia modification is 15%-20%, the preferred solid-liquid ratio is 1:6-1:8, the preferred modification temperature is 65-75℃, and the preferred modification time is 5-7h.

[0031] Furthermore, in step four, the molar ratio of amino acids to metal ions is preferably 2.2:1-2.8:1, the chelation reaction temperature is preferably 62-68℃, and the chelation time is preferably 2.5-3.5h.

[0032] Furthermore, in step five, the preferred culture temperature for Bacillus pasteurellosis is 32-34℃, and the preferred culture time is 30-40h. The preferred culture temperature for salt-tolerant phosphate-solubilizing bacteria and nitrogen-fixing bacteria is 30-32℃, and the preferred culture time is 36-48h. The preferred volume ratio of the three bacterial solutions is 2:1.2:1.

[0033] Furthermore, in step six, the preferred mass fraction of the polyglutamic acid aqueous solution is 10%–12%, the preferred mass ratio of urea to polyglutamic acid is 1:0.15–1:0.25, and the preferred spraying temperature is 55–65°C.

[0034] Furthermore, in step seven, the moisture content of the material is preferably 18%–22%, the granulation time is preferably 20–25 min, and the drying temperature is preferably 42–48℃.

[0035] The beneficial effects of the method for preparing the biological-mineral composite amendment for saline-alkali land in this invention are: it significantly enhances the activity of steel slag through alkali fusion activation technology, enabling it to be rapidly released in saline-alkali soil. Highly alkaline red mud is transformed into a functional material with high specific surface area and strong adsorption capacity through dual treatment of sulfuric acid neutralization and hydrothermal modification; a large number of alkaline functional groups are introduced into the surface of biochar through ammonia modification, thereby improving its cation exchange capacity and microbial carrier performance; the stability and bioavailability of trace elements are improved through amino acid chelation; urea slow release is achieved through polyglutamic acid encapsulation, and the MIP reaction rate is precisely controlled; the activity of functional bacteria is ensured through low-temperature granulation and drying, ensuring that the soil conditioner can effectively exert a synergistic improvement effect of mineral-organic-biological three-phase in the soil.

[0036] Compared with the prior art, the present invention has the following significant differences and technological advancements: First, the raw material systems are completely different: the comparative document uses phosphate rock tailings and low-rank coal, while this invention uses steel slag, neutralized red mud, and biochar, realizing the resource utilization of different industrial wastes. Among them, the active calcium source provided by steel slag has a significantly better reaction rate and ion exchange capacity than the acid hydrolysis products of phosphate rock tailings, the sodium-fixing capacity of the aluminosilicate gel of neutralized red mud far exceeds the chelation adsorption effect of humic acid in low-rank coal, and the cation exchange capacity and microbial carrier performance of modified biochar are significantly stronger than humic acid.

[0037] Second, a major breakthrough has been achieved in the improvement mechanism: While prior art mainly relies on chemical neutralization and ion exchange, this invention is the first to introduce the MICP biomineralization mechanism into the field of saline-alkali land improvement. Through a microbial-induced carbonate precipitation reaction driven by urease-producing bacteria, free carbonate is... and It mineralizes into stable calcium carbonate crystals, achieving a triple effect of long-lasting calcium fixation, carbon fixation, and salt fixation. The improvement effect can last for 12-24 months, which is 4-8 times longer than that of traditional modifiers.

[0038] Third, a three-level gradient improvement system is constructed: the prior art is a single-level release system, while this invention constructs a three-level gradient calcium source release and salt fixation system through alkali-activated steel slag (fast-acting), hydrothermal modified red mud (slow-release), and MIP biomineralization (reserve), ensuring the improvement of the entire soil profile from 0 to 50 cm, while the prior art mainly acts on the surface soil.

[0039] Fourth, achieving significant carbon neutrality benefits: While the prior art lacks carbon fixation capabilities, this invention, through the MICP biomineralization reaction, can fix carbon per ton of modifier. The waste volume is 15-25 kg, and the resource utilization rate of industrial waste is >90%, which meets the requirements of the carbon neutrality strategy.

[0040] Fifth, the preparation process technology routes are different: the comparative document uses acid activation and ammonia neutralization granulation, while this invention uses green processes such as alkali fusion activation, hydrothermal modification, and ammonia modification, which avoids the use of large amounts of strong acid and reduces environmental pollution. At the same time, the polyglutamic acid encapsulation and slow-release technology is used to precisely control the MIP reaction rate to ensure the stability and sustainability of the improvement effect.

[0041] Sixth, the improvement effect is significantly enhanced: the comparative document does not clearly provide specific improvement data. After 90 days of application, the present invention can reduce the pH value of severely saline-alkali land (initial pH value 10.1, conductivity 11.5 dS / m, sodium adsorption ratio 42) to 7.8, conductivity to 3.2 dS / m, and sodium adsorption ratio to 11, and increase crop yield by 40% to 60%. The improvement effect far exceeds that of traditional products.

[0042] In summary, the technical similarity between this invention and the prior art is less than 20%. It has achieved substantial innovation and significant technological progress in terms of raw material selection, improvement mechanism, system construction, carbon fixation capacity, preparation process, and improvement effect, thus meeting the high inventiveness standard for invention patents.

[0043] The beneficial effects of this invention include: First, a mineral-organic-biological three-phase synergistic system is constructed, breaking through the limitations of traditional single or binary components. Through the synergistic effect of four mechanisms—rapid ion exchange of steel slag, sodium fixation of red mud aluminosilicate gel, cation exchange of biochar, and biomineralization of MIP—the entire process of rapid improvement, slow-release salt fixation, and long-term stability is achieved. The improvement effect lasts for 12-24 months, which is 4-8 times that of traditional improvers.

[0044] Second, this study is the first to apply the MIP biomineralization mechanism to saline-alkali land improvement, utilizing urease secreted by Bacillus pasteurella to catalyze the hydrolysis of urea to produce... and In the release of steel slag Induced formation under certain conditions Precipitation mineralizes free calcium ions into stable calcium carbonate crystals, achieving long-term fixation. And sealed Each ton of improver can be fixed 15-25 kg, achieving carbon neutrality while improving saline-alkali land.

[0045] Third, establish a three-tiered calcium source release system of rapid-release, slow-release, and reserve, enabling rapid release of calcium from alkali-activated steel slag within 0-7 days. Rapid ion exchange was performed, and hydrothermally modified red mud slowly formed an aluminosilicate gel fixation over 7–60 days. MICP biomineralization continues for 60–730 days. Mineralization into calcium carbonate enables salt storage and fixation, ensuring comprehensive soil profile improvement and long-term stability across the 0-50cm layer.

[0046] Fourth, achieve high-value utilization of industrial waste, transforming industrial and agricultural solid wastes such as steel slag, red mud, and agricultural and forestry waste into high-performance saline-alkali land improvement materials. The resource utilization rate of industrial waste is >90%, reducing the land occupation and environmental pollution caused by solid waste storage, which is in line with the concept of circular economy and sustainable development.

[0047] Fifth, it significantly improves the physical and chemical properties of severely saline-alkali soils and crop growth. After 90 days of application, the pH value of severely saline-alkali soils can be reduced from 10.1 to 7.8, the electrical conductivity from 11.5 dS / m to 3.2 dS / m, the sodium adsorption ratio from 42 to 11, the soil aggregate structure increases by 35% to 50%, the organic matter content increases by 40% to 65%, and the crop yield increases by 40% to 60%, resulting in significant economic and ecological benefits.

[0048] Sixth, the preparation process is green and environmentally friendly. It adopts green processes such as alkali fusion activation, hydrothermal modification, and ammonia modification to replace traditional strong acid activation, reducing the discharge of acidic wastewater. Low-temperature granulation is used to protect the activity of functional bacteria, and polyglutamic acid encapsulation is used to achieve urea slow release. The reaction rate of MIP is precisely controlled to ensure the stable and reliable performance of the modifier. Detailed Implementation

[0049] The technical solution of the present invention will be described in detail below through specific embodiments, but it should not be construed as a limitation on the scope of protection of the present invention.

[0050] Raw materials and reagents used in the examples: Converter slag, with a free calcium oxide content of 15%–18%, sourced from Hebei Iron & Steel Group Tangshan Iron & Steel Company; Bayer process red mud, with a pH value of 11–12 and an alumina content of 20%–25%, sourced from China Aluminum Shandong Branch; straw and rice husks, sourced from farmers in Hengshui City, Hebei Province; sodium hydroxide, analytical grade, sourced from Sinopharm Chemical Reagent Co., Ltd.; sulfuric acid, analytical grade; ammonia water, mass fraction 25%; zinc sulfate, ferrous sulfate, manganese sulfate, and boric acid, chemically pure, sourced from Aladdin Reagent Co., Ltd.; compound amino acids, with an amino acid content >40%; urea, agricultural grade, with a nitrogen content of 46%, sourced from Shandong Luxi Chemical Co., Ltd.; γ-polyglutamic acid, molecular weight 50–200 kDa; sodium carboxymethyl cellulose, degree of substitution 0.7–0.8, sourced from Shanghai Maclean Biochemical Technology Co., Ltd.

[0051] Microbial strains: *Sporosarcina pasteurii*, CGMCC number 1.3687, purchased from the China General Microbiological Culture Collection Center; *Bacillus megaterium*, a salt-tolerant phosphate-solubilizing bacterium isolated and screened from saline-alkali soil in the laboratory; *Azospirilluma estuarii*, a salt-tolerant nitrogen-fixing bacterium, CGMCC number 1.17325, purchased from the China General Microbiological Culture Collection Center.

[0052] Main instruments and equipment: High-pressure reactor, WHF-0.5 type; Tube furnace, OTF-1200X type; Spray dryer, B-290 type; Disc granulator, D1000 type; Fluidized bed dryer, FG-30 type; X-ray diffractometer, D8 Advance type; Specific surface area analyzer, ASAP 2460 type; Scanning electron microscope, SU8010 type.

[0053] Example 1: The steps for preparing alkali-activated steel slag powder in this example are as follows: 10 kg of converter steel slag was crushed to a particle size of <5 mm and mixed with a 30% sodium hydroxide solution at a solid-liquid ratio of 1:3. The mixture was placed in a 50 L high-pressure reactor, sealed, and reacted at 140 °C and 0.3 MPa pressure for 3.5 h, with stirring every 30 min to ensure uniform reaction. After the reaction, the mixture was allowed to cool naturally to room temperature. The solid and liquid phases were separated using a plate and frame filter press. The solid phase was washed with deionized water until the pH of the filtrate was 8.5. The filtrate was then dried in a 108 °C forced-air drying oven for 6 h to constant weight. After being pulverized using a Raymond mill and passed through a 120 mesh sieve, 8.2 kg of alkali-activated steel slag powder was obtained, with a yield of 82%.

[0054] X-ray diffraction analysis of the phase composition of steel slag before and after alkali fusion activation showed that the main phase of the untreated steel slag was dicalcium silicate. Tricalcium silicate ( ), tetracalcium aluminoferrite ( ) and free calcium oxide ( The original steel slag has a complete and dense lattice. After alkali fusion activation, the silicate lattice structure of the steel slag is significantly depolymerized, and the characteristic broad peaks of hydrated calcium silicate gel appear. The free calcium oxide content increases from 16% to 25% of the original steel slag, and the active calcium index (determined by the citric acid-sucrose method) increases from 0.45 to 0.85, proving that alkali fusion activation significantly improves the activity of the steel slag.

[0055] The chemical composition of alkali-activated steel slag powder was determined by chemical analysis, and the results are shown in Table 1.

[0056] Table 1 Chemical Composition of Alkali-Fused Activated Steel Slag Powder

[0057] Example 2: The steps for preparing hydrothermally modified neutralized red mud in this example are as follows: Take 5 kg of Bayer red mud (approximately 20% moisture content) and mix it with a 15% sulfuric acid solution at a solid-liquid ratio of 1:4.5. Stir and neutralize in a mechanically stirred reactor at room temperature for 60 min, measuring the pH value every 10 min. Stop adding acid when the pH value stabilizes at 7.2. After neutralization, filter the slurry through a plate and frame filter press. Wash the filter cake with deionized water and add it to the filtrate. Concentration (determined by barium sulfate turbidimetric method) <300mg / L.

[0058] The washed and neutralized red mud filter cake was mixed with deionized water at a solid-liquid ratio of 1:2 to form a slurry. This slurry was transferred to a 10L hydrothermal reactor, sealed, and hydrothermally treated at 170℃ and 1MPa pressure for 4 hours, with the stirring rate maintained at 100 r / min throughout the reaction. After hydrothermal treatment, the mixture was allowed to cool naturally to room temperature. The slurry was then dried in a 110℃ forced-air drying oven for 9 hours until constant weight was achieved. After pulverizing using a ball mill and passing through a 200-mesh sieve, 3.8 kg of hydrothermally modified neutralized red mud was obtained, with a yield of 76%.

[0059] The specific surface area of ​​neutralized red mud before and after hydrothermal modification was measured using a specific surface area analyzer. The results showed that the specific surface area of ​​unmodified neutralized red mud was 28 m² / g, the pore volume was 0.09 cm³ / g, and the average pore diameter was 12.5 nm. After hydrothermal modification, the specific surface area of ​​neutralized red mud increased to 65 m² / g, the pore volume increased to 0.23 cm³ / g, and the average pore diameter was 6.8 nm, which is a typical mesoporous structure. This proves that hydrothermal modification significantly promotes the development of the pore structure of red mud.

[0060] The microstructure of hydrothermally modified neutralized red mud was observed using scanning electron microscopy. At magnifications of 5000x and 20000x, the modified red mud exhibited a loose, porous, lamellar structure with lamellar thicknesses of approximately 50-200 nm. The lamellars interweave to form a three-dimensional network framework. This unique microstructure... The adsorption and immobilization provide abundant active sites.

[0061] The chemical composition of hydrothermally modified neutralized red mud was determined by chemical analysis, and the results are shown in Table 2.

[0062] Table 2 Chemical composition of hydrothermally modified neutralized red mud

[0063] Example 3: The steps for preparing basic functional group modified biochar in this example are as follows: Take 5 kg of corn stalks, crush them to a particle size <3 mm, and dry them in a 105℃ forced-air drying oven until the moisture content is <5%. Place the dried stalks into a quartz boat, put it into a tube furnace, purge with nitrogen (flow rate 200 mL / min) to purge air for 15 min, then heat to 580℃ at a rate of 8℃ / min, and pyrolyze at this constant temperature for 2 h. After cooling, remove the pyrolyte to obtain 1.4 kg of primary biochar, with a biochar yield of 28%.

[0064] Primary biochar was mixed with an 18% ammonia solution at a solid-liquid ratio of 1:7 and placed in a three-necked flask equipped with a reflux condenser. The mixture was stirred and impregnated for 6 hours under oil bath heating at 70°C, with a suitable amount of ammonia added every hour to maintain a stable ammonia concentration. After modification, the mixture was separated by suction filtration using a Buchner funnel. The solid phase was washed with deionized water until the pH of the filtrate reached 8.5, and then dried in a 90°C forced-air drying oven until the moisture content was <3%. The resulting product was then pulverized and passed through a 60-mesh sieve to obtain 1.1 kg of basic functionalized modified biochar, with a yield of 79%.

[0065] The elemental composition of biochar before and after modification was determined using an elemental analyzer. The results showed that the primary biochar had a carbon content of 72.3%, a nitrogen content of 1.2%, a hydrogen content of 3.5%, and an oxygen content of 20.8%. After modification, the carbon content of the biochar decreased to 68.5%, the nitrogen content increased to 5.8%, the hydrogen content was 4.1%, and the oxygen content was 20.3%, proving that ammonia modification successfully introduced nitrogen-containing functional groups into the biochar.

[0066] The cation exchange capacity of biochar before and after modification was determined by the cation exchange capacity assay (ammonium acetate method, pH 7). The results showed that the cation exchange capacity of primary biochar was 42 cmol / kg, while that of modified biochar increased to 85 cmol / kg, an increase of 102%. This demonstrates that the introduction of basic functional groups significantly enhances the ion exchange capacity of biochar.

[0067] The specific surface area of ​​the modified biochar was measured to be 250 m² / g, the pore volume was 0.18 cm³ / g, and the average pore size was 2.9 nm. The well-developed pore structure provides a good microenvironment for microbial colonization.

[0068] Example 4 The steps for preparing amino acid-chelated trace elements in this embodiment are as follows: In a reactor equipped with mechanical stirring and temperature control, zinc sulfate (containing...) was weighed out at a mass ratio of 1:2:0.6:0.4. 23%) 200g, ferrous sulfate (containing 20%) 400g, manganese sulfate (containing Dissolve 120g of 31% boric acid (containing 7.5% B1) and 80g of boric acid in 5L of deionized water to prepare a mixed trace element solution with a total concentration of 80g / L.

[0069] Weigh 800g of composite amino acid powder (containing 45% free amino acids, mainly glutamic acid, glycine, and alanine) and add it to the above trace element solution. At this point, the molar ratio of amino acids to metal ions is approximately 2.5:1. Under mechanical stirring, slowly add sodium hydroxide solution to adjust the pH to 6.5, raise the temperature to 65℃, maintain the temperature, and continuously stir the chelation reaction for 3 hours. During the reaction, measure the pH every 30 minutes and adjust it to 6.5.

[0070] After the chelation reaction was completed, the mixture was cooled to room temperature and then spray-dried using a spray dryer with an inlet air temperature of 180°C, an outlet air temperature of 80°C, and an atomization pressure of 0.2 MPa. This yielded 1.2 kg of pale yellow amino acid chelated trace element powder, with a yield of 85%.

[0071] The chelation rate of metal ions in the chelation products was determined by ultraviolet-visible spectrophotometry. The results showed that the chelation rate of zinc was 88%, that of iron was 85%, that of manganese was 82%, and that of boron was 75%, proving that amino acids have a good chelation effect on metal ions.

[0072] Example 5 The steps for preparing the compound functional microbial agent in this embodiment are as follows: Culture of Bacillus pasteurellii: Urea medium (composition: peptone 20 g / L) was used. 5g / L, urea 20g / L 2.12 g / L 10 g / L of *Bacillus pasteurellii* strain (containing 0.2 g / L yeast extract, pH 9) was inoculated into 100 mL of seed culture medium and cultured at 33℃ with shaking at 180 rpm for 24 h. Then, 5% of the culture was inoculated into 5 L of fermentation medium and cultured at 33℃ with shaking at 150 rpm for 36 h until the late logarithmic growth phase. At this point, the optical density (600 nm wavelength) of the bacterial solution was 2.8, and the viable cell count was [missing information]. per mL.

[0073] Culture of salt-tolerant phosphate-solubilizing bacteria: Inorganic phosphate medium (composition: glucose 10g / L) was used. 0.5g / L 5g / L 0.2g / L, 0.3g / L 0.01g / L 5 g / L, pH 7), the preserved Bacillus phosphate-solubilizing strain was inoculated into 100 mL of seed culture medium and cultured at 30℃ and 180 rpm for 24 h with shaking. Then, 5% of the inoculum was inoculated into 5 L of fermentation medium and cultured at 30℃ and 150 rpm for 40 h with shaking. At this point, the optical density of the bacterial culture was 2.5, and the viable cell count was [missing value]. per mL.

[0074] Culture of salt-tolerant nitrogen-fixing bacteria: A nitrogen-free culture medium (composition: sucrose 10 g / L) was used. 0.5g / L 0.2g / L, 0.1g / L, 0.05g / L 0.01 g / L (pH 7) of the preserved *Azotocinus* strain was inoculated into 100 mL of seed culture medium and cultured at 30 °C with shaking at 180 rpm for 24 h. Then, 5% of the inoculum was inoculated into 5 L of fermentation medium and cultured at 30 °C with shaking at 150 rpm for 48 h. At this point, the optical density of the bacterial culture was 2.2, and the viable cell count was [missing value]. per mL.

[0075] The three cultured bacterial suspensions were centrifuged at 8000 rpm for 10 min to collect the bacterial cells, and then resuspended in sterile physiological saline to a bacterial suspension concentration of [missing value]. The bacterial suspension was prepared by mixing three bacterial suspensions at a volume ratio of 2:1.2:1. Sodium alginate (3% by mass) and skim milk powder (2% by mass) were added as preservatives. After thorough mixing, the mixture was freeze-dried using a freeze dryer. The pre-freezing temperature was -40℃ for 6 hours, the sublimation drying temperature was -20℃ for 24 hours, and the desorption drying temperature was 20℃ for 6 hours, yielding 300g of a pale yellow composite functional bacterial powder with a total viable count of [missing information]. per g.

[0076] The urease activity of Bacillus pasteurellium in the bacterial powder was determined to be 62 U / g of bacterial powder using the urease activity assay (phenol-sodium hypochlorite colorimetric method), which meets the requirements of the MICP reaction for urease activity.

[0077] Example 6 The steps for preparing polyglutamic acid-encapsulated sustained-release urea in this embodiment are as follows: Weigh 5 kg of urea granules (particle size 2-3 mm, nitrogen content 46%) and load them into a fluidized bed coating machine, preheating them to 40°C under fluidized conditions. Dissolve 600 g of γ-polyglutamic acid (molecular weight 100 kDa) in 4000 mL of deionized water to prepare an 11% (w / w) polyglutamic acid aqueous solution.

[0078] The fluidized bed coating machine was started, with the inlet air temperature set to 60℃ and the fluidization velocity to 0.8 m / s. Polyglutamic acid solution was uniformly sprayed onto the surface of fluidized urea granules using a dual-fluid spray gun at a spray rate of 20 mL / min and an atomization pressure of 0.2 MPa. The spraying process lasted 45 min. After spraying, fluidized bed drying continued for 15 min. The granules were then discharged and dried in a 60℃ forced-air drying oven until the moisture content was <1.5%, yielding 5.4 kg of slow-release urea granules coated with a polyglutamic acid film, representing a coating weight gain of 8%.

[0079] The nitrogen release characteristics of sustained-release urea were determined using the dissolution curve method: 10g of coated urea was weighed and placed in 500mL of deionized water, and allowed to stand at a constant temperature of 25℃. Samples were taken on days 1, 3, 7, 14, 21, and 28 to measure the urea nitrogen concentration in the water, and the cumulative release rate was calculated. The results showed that the cumulative release rate was 12% on day 1, 35% on day 7, 62% on day 14, 85% on day 21, and 96% on day 28, demonstrating that polyglutamic acid encapsulation achieved a slow and sustained release of urea.

[0080] Example 7 This embodiment prepares a biological-mineral composite amendment for saline-alkali land according to the following formula and steps: Formula composition (parts by weight): 45 parts of alkali-activated steel slag powder (prepared according to the method in Example 1) 25 parts of hydrothermally modified neutralized red mud (prepared according to the method in Example 2), 12 portions of alkaline functional group modified biochar (prepared according to the method in Example 3) Four portions of amino acid chelated trace elements (prepared according to the method in Example 4) 8 parts of compound functional microbial agent (prepared according to the method in Example 5), 15 portions of polyglutamic acid-encapsulated sustained-release urea (prepared according to the method in Example 6) 3 parts of sodium carboxymethyl cellulose binder.

[0081] Preparation steps: Accurately weigh 4500g of alkali-fused activated steel slag powder, 2500g of hydrothermally modified neutralized red mud, 1200g of alkaline functional group modified biochar, 400g of amino acid chelated trace elements, and 1500g of polyglutamic acid-encapsulated slow-release urea according to the formula ratio. Add them to a high-speed mixer, set the mixing speed to 600r / min, and the mixing time to 8min to ensure that all components are fully and uniformly mixed. Then add 800g of compound functional microbial agent, reduce the mixing speed to 300r / min, and mix for another 2min to avoid high-speed shearing damage to the functional microorganisms.

[0082] Dissolve 300g of sodium carboxymethyl cellulose in 7000mL of deionized water to prepare a 4% (w / w) binder solution, and stir thoroughly until completely dissolved and transparent.

[0083] Transfer the uniformly mixed solid material to a disc granulator. Set the disc tilt angle to 45° and the disc rotation speed to 30 r / min. After starting the disc granulator, spray the binder solution evenly through the spray system at a spray rate of 100 mL / min. Closely observe the granulation of the material during the spraying process. Stop spraying when most of the material forms 2-5 mm particles. At this time, the moisture content of the material is about 20%, and the granulation time is 22 min.

[0084] The granulated wet granules were transferred to a low-temperature fluidized bed dryer, with the inlet air temperature set at 45℃ and the fluidizing air velocity at 0.6 m / s. Drying was carried out until the material moisture content was <8%, with a drying time of approximately 45 minutes. The dried granules were then sieved through a vibrating screen, and finished granules with a particle size of 2–4 mm were collected, yielding 9200 g of saline-alkali land biological-mineral composite conditioner, with a granulation rate of 92%.

[0085] The finished modifier is packaged in aluminum foil composite bags, vacuum sealed, and stored at room temperature away from light for later use.

[0086] The physicochemical properties of the finished product modifier were determined, and the results are shown in Table 3.

[0087] Table 3. Physicochemical properties of the saline-alkali land biological-mineral composite amendment prepared in Example 7.

[0088] Example 8: The following formulation and steps were used to prepare a biological-mineral composite amendment for saline-alkali land: Formula composition (parts by weight): 30 parts of alkali-activated steel slag powder 15 parts of hydrothermal modified and neutralized red mud Eight parts of alkaline functional group modified biochar. Two portions of amino acid chelated trace elements. 5 parts of compound functional microbial agent, Ten portions of polyglutamic acid-encapsulated sustained-release urea were used. Two parts of sodium carboxymethyl cellulose binder.

[0089] The modifier was prepared according to the same preparation steps and process parameters as in Example 7, and 6100g of finished product was obtained with a granulation rate of 89%.

[0090] Example 9 This embodiment prepares a biological-mineral composite amendment for saline-alkali land according to the following formula and steps: Formula composition (parts by weight): 60 parts of alkali-activated steel slag powder 35 parts of hydrothermal modified and neutralized red mud 18 parts of alkaline functional group modified biochar. Six portions of amino acid chelated trace elements. 12 parts of compound functional microbial agent, 20 portions of polyglutamic acid-encapsulated sustained-release urea. Five parts of sodium carboxymethyl cellulose binder.

[0091] The modifier was prepared according to the same preparation steps and process parameters as in Example 7, and 13,800 g of finished product was obtained with a granulation rate of 91%.

[0092] Example 10 This embodiment prepares a biological-mineral composite amendment for saline-alkali land according to the following formula and steps: Formula composition (parts by weight): 50 parts of alkali-activated steel slag powder 28 parts of hydrothermal modified and neutralized red mud 14 portions of alkaline functional group modified biochar. 4.5 parts of amino acid chelated trace elements Nine portions of compound functional microbial agent, Sixteen portions of polyglutamic acid-encapsulated sustained-release urea were used. 3.5 parts of sodium carboxymethyl cellulose binder.

[0093] The modifier was prepared according to the same preparation steps and process parameters as in Example 7, and 11200g of finished product was obtained with a granulation rate of 93%.

[0094] Comparative Example 1 This comparative example uses the formula and method disclosed in prior art document CN111303896A to prepare a saline-alkali soil conditioner: Take 5 kg of phosphate rock tailings and mix it with 4.5 kg of 98% sulfuric acid and 1 kg of water at a mass ratio of 1:0.9:0.2. Mature the mixture in a sealed maturation silo at 50℃ for 15 days to obtain a powdery material. Grind lignite to 60 mesh using a wet grinding method to prepare a coal slurry with a moisture content of 60%. Take 1 kg of the coal slurry (dry basis) and mix it with 667 g of 60% nitric acid at a dry basis to nitric acid mass ratio of 1:0.4. React the mixture in a sealed reactor at 80℃ for 0.5 h. Add 1 g of boric acid, 1 g of zinc oxide, 1 g of ferrous oxide, and 1 g of manganese dioxide, and continue the reaction for 5 min to obtain a mixed slurry. Mix the mixed slurry and the powdery material at a mass ratio of 1:2 and granulate. During the granulation process, ammonia gas is introduced to adjust the pH to 3-4. After granulation, dry and sieve the mixture, and spray it with a compound inoculant of Bacillus subtilis, Bacillus megaterium, and Aspergillus niger to obtain a comparative example improver.

[0095] Comparative Example 2 This comparative example prepares a mineral-organic composite amendment for saline-alkali land that does not contain compound functional microbial agents: Formula composition (by weight): 45 parts of alkali-fused activated steel slag powder, 25 parts of hydrothermally modified neutralized red mud, 12 parts of alkaline functional group modified biochar, 4 parts of amino acid chelated trace elements, 15 parts of polyglutamic acid-encapsulated slow-release urea, and 3 parts of sodium carboxymethyl cellulose binder.

[0096] The modifier was prepared according to the same preparation steps and process parameters as in Example 7, but without the addition of the compound functional bacterial agent, to obtain the modifier of Comparative Example 2.

[0097] Comparative Example 3 This comparative preparation of a saline-alkali land biological-mineral composite amendment without polyglutamic acid-encapsulated slow-release urea: Formula composition (by weight): 45 parts of alkali-fused activated steel slag powder, 25 parts of hydrothermally modified neutralized red mud, 12 parts of alkaline functional group modified biochar, 4 parts of amino acid chelated trace elements, 8 parts of composite functional bacterial agent, and 3 parts of sodium carboxymethyl cellulose binder.

[0098] The modifier was prepared according to the same preparation steps and process parameters as in Example 7, but without the addition of polyglutamic acid to encapsulate the sustained-release urea, thus obtaining the modifier of Comparative Example 3.

[0099] Application Experiment 1: Evaluation of the Effect of Improving the Physicochemical Properties of Saline-Alkali Soil Experimental site: Severely saline-alkali land experimental field in Nanpi County, Cangzhou City, Hebei Province, with soil type being coastal saline tidal soil.

[0100] Experimental Design: A randomized block design was adopted, with 5 treatments: Treatment 1 was a blank control (no amendment applied), Treatment 2 was the amendment from Comparative Example 1 (application rate of 1000 kg / mu), Treatment 3 was the amendment from Comparative Example 2 (application rate of 1000 kg / mu), Treatment 4 was the amendment from Example 7 (application rate of 800 kg / mu), and Treatment 5 was the amendment from Example 7 (application rate of 1000 kg / mu). Each treatment had 3 replicate plots, each plot having an area of ​​66.7 m² (10 m × 6.67 m).

[0101] Experimental Methods: The soil amendment was applied on March 20, 2024. It was applied manually and evenly to the soil surface of the plot, then tilled to a depth of 20 cm using a rotary tiller to ensure thorough mixing. Irrigation was performed once after the amendment application, with an irrigation rate of 60 m³ / mu. Soil samples were collected at depths of 0-20 cm and 20-50 cm at 30, 60, and 90 days after application. Soil pH (soil-to-water ratio 1:2.5, pH meter method), electrical conductivity (soil-to-water ratio 1:5, electrical conductivity meter method), and sodium adsorption ratio (dissolved sodium using flame photometry) were measured. , , According to the formula Calculation), organic matter content (potassium dichromate oxidation method), and agglomerate content (wet sieving method to determine water-stable agglomerates >0.25mm).

[0102] The test results are shown in Tables 4 and 5.

[0103] Table 4. Soil physicochemical properties in the 0-20cm soil layer 90 days after application.

[0104] Note: Before application, the initial soil pH was 10.1, electrical conductivity was 11.5 dS / m, sodium adsorption ratio was 42, organic matter was 6.1 g / kg, and aggregate structure was 8.3%.

[0105] Table 5. Soil physicochemical properties in the 20–50 cm soil layer 90 days after application.

[0106] Note: Before application, the initial pH value of the soil layer 20-50cm was 10.2, the electrical conductivity was 12.0 dS / m, the sodium adsorption ratio was 43.5, and the organic matter content was 5.7 g / kg.

[0107] As can be seen from the results in Tables 4 and 5, treatment 5 (amort from Example 7, 1000 kg / mu) showed the most significant improvement effect. After 90 days of application, the pH value of the 0-20cm soil layer decreased from 10.1 to 7.8, a decrease of 22.5%; the electrical conductivity decreased from 11.5 dS / m to 3.2 dS / m, a decrease of 72.2%; the sodium adsorption ratio decreased from 42 to 11.2, a decrease of 73.3%; the organic matter content increased from 6.1 g / kg to 16.8 g / kg, an increase of 175.4%; and the aggregate content increased from 8.3% to 32.6%, an increase of 292.8%.

[0108] The treatment of five soil layers at a depth of 20–50 cm also showed good improvement effects. The pH value decreased from 10.2 to 8.3, a reduction of 18.6%; the electrical conductivity decreased from 12.0 dS / m to 5.5 dS / m, a reduction of 54.2%; the sodium adsorption ratio decreased from 43.5 to 18.3, a reduction of 57.9%; and the organic matter content increased from 5.7 g / kg to 11.8 g / kg, an increase of 106.9%. This proves that the soil conditioner of this invention can achieve full-layer improvement of the soil profile from 0 to 50 cm.

[0109] The second control (comparative treatment 1) only had a certain improvement effect on the top 0-20cm soil layer, and the improvement effect on the 20-50cm deep soil layer was very weak. The pH value decreased by only 0.4 units and the electrical conductivity decreased by only 1.5 dS / m, which proves that the traditional soil amendment mainly acts on the top 0-20cm soil layer and has insufficient ability to improve the deep soil layer.

[0110] The improvement effect of treatment 3 (comparative example 2 improver, without compound functional microbial agent) was significantly weaker than that of treatment 5, proving that the MIP biomineralization mechanism driven by compound functional microbial agent plays an important role in the improvement of saline-alkali land.

[0111] Application Experiment 2: Verification of the Effect of MIP Biomineralization on Calcium and Carbon Fixation Experimental Methods: A soil column simulation test was conducted, with four treatments: Treatment 1 was a blank control soil; Treatment 2 was soil with the addition of the amendment from Comparative Example 2 (without inoculant); Treatment 3 was soil with the addition of the amendment from Example 7; and Treatment 4 was soil with the addition of the amendment from Example 7 plus exogenous supplementation. The soil. Each treatment was set up with 3 replicates.

[0112] Take 5 kg of severely saline-alkali soil (pH 10.2, electrical conductivity 12.0 dS / m), sieve it through a 2 mm sieve to remove impurities, and mix it thoroughly with the soil amendment at a ratio of 1 g per kilogram of soil. Fill the mixture into an acrylic glass soil column with an inner diameter of 10 cm and a height of 50 cm, controlling the filling density to 1.3 g / cm³. Lay a filter screen and gravel layer at the bottom of the soil column for drainage. Treatment four involves adding soil amendment while simultaneously supplementing... Solution (providing additional 500 mg / kg soil). The soil column was incubated in a constant temperature incubator at 25°C. Every 7 days, 200 mL of deionized water was rinsed from the top, and the eluent was collected for analysis.

[0113] After 90 days of cultivation, stratified samples were taken to analyze the calcium carbonate content in the soil (hydrochloric acid dissolution-EDTA titration method) and free calcium carbonate. Content (atomic absorption spectrometry) and microbial biomass (plate count method) were determined. Simultaneously, X-ray diffraction was used to analyze the calcium carbonate crystal form in the soil, and scanning electron microscopy was used to observe the microstructure of the MIP mineralization products.

[0114] The test results are shown in Table 6.

[0115] Table 6. Analysis of MIP mineralization products in soil after 90 days of cultivation.

[0116] Note: Fixed quantity The increment is calculated by multiplying by 0.44 (the mass fraction of carbon in calcium carbonate).

[0117] As shown in Table 6, the increase in calcium carbonate in soil treated with the third treatment (using the amendment in Example 7) reached 3.65 g / kg soil, which is 4.5 times that of control sample two (without the inoculant) and 24.3 times that of the blank control. This demonstrates that the MIP biomineralization reaction driven by the compound functional inoculant significantly promotes calcium carbonate formation. (Treatment 3 free...) The content decreased to 185 mg / kg soil, a 43.1% reduction compared to control example two, proving that the MIP reaction effectively immobilized free [unspecified substance]. The treatment of three microbial biomass reached The number of microorganisms per g of soil was 6.9 times that of the blank control, demonstrating that the modified biochar provided a favorable habitat for microorganisms. (Treatment three-fixation) The concentration reached 1.606 g / kg soil. Based on an application rate of 1000 kg / mu, a tillage depth of 20 cm, and a soil bulk density of 1.3 g / cm³, this is equivalent to a fixed amount per mu. 41.8kg.

[0118] X-ray diffraction analysis showed that the main crystal form of calcium carbonate in the three soil treatments was calcite. Characteristic diffraction peaks of calcite appeared at 29.4°, 36.0°, 43.2°, 47.5°, and 48.5°. The peaks were sharp and intense, proving that the calcium carbonate crystals generated by the MICP reaction had good crystallinity.

[0119] Scanning electron microscopy revealed a large number of rhombohedral calcium carbonate crystals, ranging in size from 5 to 20 μm, distributed on the surface and in the pores of the soil particles in the three treatments. These calcium carbonate crystals act as bridges, cementing the loose soil particles together to form stable aggregate structures. Numerous rod-shaped bacterial cells (2-5 μm in length and 0.5-1 μm in diameter) were observed on and around the calcium carbonate crystals, demonstrating that Bacillus pasteurellii played a nucleation center role in the formation of calcium carbonate precipitation.

[0120] Application Experiment 3: Evaluation of Crop Growth and Yield Effects in Saline-Alkali Land Experimental site: Severely saline-alkali land experimental field in Nanpi County, Cangzhou City, Hebei Province; the test crop was maize (variety Zhengdan 958).

[0121] Experimental Design: A randomized block design was adopted, with 5 treatments: Treatment 1 was a blank control; Treatment 2 was applied with conventional fertilizer (urea 20 kg / mu, diammonium phosphate 15 kg / mu, potassium chloride 10 kg / mu); Treatment 3 was applied with 1000 kg / mu of amendment from Comparative Example 1 plus half the amount of conventional fertilizer; Treatment 4 was applied with 800 kg / mu of amendment from Example 7 plus half the amount of conventional fertilizer; and Treatment 5 was applied with 1000 kg / mu of amendment from Example 7 plus half the amount of conventional fertilizer. Each treatment had 3 replicate plots, each plot having an area of ​​66.7 m².

[0122] Experimental Methods: On April 10, 2024, soil conditioner and fertilizer were applied and mixed thoroughly by rotary tillage. Corn was sown on April 15 with a row spacing of 60 cm and a plant spacing of 25 cm, resulting in a planting density of 4400 plants per mu (approximately 667 square meters). Normal management was implemented during the growth period. Plant height, stem diameter, leaf area index, aboveground dry matter, and root dry weight were measured at the seedling, jointing, tasseling, and maturity stages. Yield was measured at maturity based on the actual harvest from each plot, and yield components such as grain moisture content, thousand-grain weight, ear length, ear diameter, number of rows, and number of grains were also measured.

[0123] The experimental results are shown in Tables 7 and 8.

[0124] Table 7. Maize Growth Indicators (Measured at the Tasseling Stage)

[0125] Table 8. Corn Yield and Yield Components

[0126] The results in Tables 7 and 8 show that the corn under treatment 5 (1000 kg / mu of improver from Example 7 plus half the amount of chemical fertilizer) grew best. The plant height, stem diameter, leaf area index, aboveground dry weight, and root dry weight were all significantly higher than those of other treatments. The final grain yield reached 682 kg / mu, which was 266.7% higher than the blank control, 40.6% higher than the conventional chemical fertilizer treatment, and 24.5% higher than the control group. This demonstrates that the improver of this invention has excellent yield-increasing effects on saline-alkali land.

[0127] It is worth noting that treatment five still achieved the highest yield despite halving the amount of chemical fertilizer applied, indicating that the amino acid chelated trace elements, compound functional microbial agents, and slow-release urea in the fertilizer improver worked synergistically to significantly improve nutrient utilization efficiency and achieve the goal of reducing fertilizer use while increasing yield.

[0128] Application Experiment 4: Evaluation of the Sustainability of Improvement Effects Experimental method: Based on the application of Experiment 1, the changes in soil physicochemical properties were monitored at 180d, 360d, 540d and 720d after the application of the amendment from Example 7 (1000kg / mu) to evaluate the sustainability of the amendment effect.

[0129] The test results are shown in Table 9.

[0130] Table 9. Changes in the physicochemical properties of soil in the 0-20cm soil layer at different times.

[0131] As shown in Table 9, after applying the soil conditioner from Example 7, the soil's physical and chemical properties continued to improve, reaching their optimal improvement effect between 90 and 180 days, and then remaining relatively stable. At 360 days, the pH was 7.4, the electrical conductivity was 2.5 dS / m, and the sodium adsorption ratio was 8.5, all remaining within the range suitable for crop growth. Even at 720 days (2 years), the soil pH was 7.6, the electrical conductivity was 2.8 dS / m, and the sodium adsorption ratio was 9.2, still significantly better than the pre-application levels, proving that the conditioner's improvement effect can last for 12-24 months, far exceeding the duration of traditional conditioners.

[0132] The long-term stability of the improved effect is mainly attributed to: First, the MIP biomineralization reaction will free First, mineralization into stable calcium carbonate crystals achieves long-term calcium fixation, preventing calcium ions from being leached or re-released; second, the hydrated aluminosilicate gel network provides physical encapsulation and chemical fixation. First, it blocks the upward migration of salts; second, modified biochar provides a lasting cation exchange capacity and a slow-release effect of organic matter; and third, the compound functional microbial agent colonizes and reproduces in the soil, continuously playing a role in phosphorus solubilization, nitrogen fixation, and MIP mineralization.

[0133] This invention fully demonstrates the technical feasibility and excellent effects of the bio-mineral composite amendment for saline-alkali land prepared from industrial waste and its preparation method through examples and application tests. It has important application value and industrialization prospects for ecological restoration of saline-alkali land, resource utilization of industrial solid waste and implementation of carbon neutrality strategy.

[0134] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention.

Claims

1. A bio-mineral composite amendment for saline-alkali land prepared using industrial waste, characterized in that, The components include the following parts by weight: 30-60 parts of alkali-activated steel slag powder 15-35 parts of hydrothermal modified and neutralized red mud 8-18 parts of alkaline functional group modified biochar. 2-6 parts of amino acid chelated trace elements 5-12 parts of compound functional microbial agent, Polyglutamic acid-encapsulated sustained-release urea, 10-20 parts. Sodium carboxymethyl cellulose binder, 2-5 parts; The alkaline-activated steel slag powder is prepared by alkaline-activated treatment of converter steel slag with sodium hydroxide solution at 120-160℃. The particle size is 80-200 mesh, the free calcium oxide content is 18%-32%, and the active calcium index is 0.7-0.

95.

2. The saline-alkali land biological-mineral composite amendment prepared from industrial waste according to claim 1, characterized in that, The hydrothermally modified neutralized red mud is prepared by neutralizing Bayer process red mud with sulfuric acid, followed by hydrothermal modification at 150-190℃ and 0.5-1.5MPa pressure for 2-6 hours. The particle size is 100-300 mesh, the alumina content is 25%-40%, and the specific surface area is 40-85m² / g. The alkaline functional group modified biochar is prepared by pyrolysis of agricultural and forestry waste at 500-650℃ with limited oxygen followed by ammonia impregnation and modification. It has a particle size of 40-120 mesh, a specific surface area of ​​150-350 m² / g, a cation exchange capacity of 50-120 cmol / kg, and a pH value of 9-11. The amino acid chelated trace elements include 0.5%–1.5% amino acid chelated zinc, 1%–3% amino acid chelated iron, 0.3%–1% amino acid chelated manganese, and 0.2%–0.8% amino acid chelated boron. The compound functional microbial agent includes a live count of Bacillus pasteurellium. Cells / g, viable count of salt-tolerant phosphate-solubilizing bacteria Cells / g, viable count of salt-tolerant nitrogen-fixing bacteria CFU / g, of which Bacillus pasteurellii can secrete urease to catalyze the hydrolysis of urea to produce and In the release of steel slag Induced formation under certain conditions Precipitation, achieving a microbially induced carbonate precipitation reaction; The polyglutamic acid-encapsulated slow-release urea is prepared by encapsulating urea with γ-polyglutamic acid, and the urea nitrogen content is 35%–45%. It can be continuously released in the soil for 15–30 days. The sodium carboxymethyl cellulose binder has a degree of substitution of 0.6-0.9 and a viscosity of 300-800 mPa·s.

3. The saline-alkali land biological-mineral composite amendment prepared from industrial waste according to claim 1, characterized in that, The alkali-fused activated steel slag powder comprises 40-50 parts by weight, the hydrothermally modified neutralized red mud comprises 20-30 parts by weight, the alkaline functional group modified biochar comprises 10-15 parts by weight, the amino acid chelated trace elements comprises 3-5 parts by weight, the composite functional bacterial agent comprises 7-10 parts by weight, the polyglutamic acid-encapsulated slow-release urea comprises 12-18 parts by weight, and the sodium carboxymethyl cellulose binder comprises 3-4 parts by weight.

4. The saline-alkali land biological-mineral composite amendment prepared from industrial waste according to claim 1, characterized in that, The free calcium oxide content of the alkali-fused activated steel slag powder is 22%–28%, and the active calcium index is 0.8–0.

9. The specific surface area of ​​the hydrothermally modified neutralized red mud is 55-75 m² / g, and the alumina content is 30%-36%.

5. The saline-alkali land biological-mineral composite amendment prepared from industrial waste according to claim 1, characterized in that, The alkaline functional group modified biochar has a cation exchange capacity of 70-100 cmol / kg and a specific surface area of ​​200-300 m² / g.

6. The method for preparing the saline-alkali land biological-mineral composite amendment prepared from industrial waste according to any one of claims 1 to 5, characterized in that, Includes the following steps: Step 1, Preparation of Alkali-Activated Steel Slag Powder: Converter steel slag is crushed to a particle size <5mm, mixed with a sodium hydroxide solution of 20%–40% by mass at a solid-liquid ratio of 1:2–1:4, placed in a high-pressure reactor, and reacted at 120–160℃ and 0.2–0.5MPa pressure for 2–5 hours. After cooling, the mixture is filtered and separated. The solid phase material is washed with deionized water until the pH value is 8–9, dried at 105–110℃ for 4–8 hours, and then crushed through an 80–200 mesh sieve to obtain alkali-activated steel slag powder. Step 2, Preparation of hydrothermally modified and neutralized red mud: Bayer process red mud is mixed with a 10%–20% sulfuric acid solution at a solid-liquid ratio of 1:3–1:6, stirred and neutralized for 30–90 minutes until the pH value is 6–8, filtered and washed into the filtrate. With a concentration <500mg / L, the neutralized red mud slurry was placed in a hydrothermal reactor and hydrothermally treated for 2-6 hours at 150-190℃ and 0.5-1.5MPa pressure. After cooling, it was dried at 100-120℃ for 6-12 hours and then pulverized through a 100-300 mesh sieve to obtain hydrothermally modified neutralized red mud. Step 3, Preparation of alkaline functional group modified biochar: Agricultural and forestry waste is crushed to a particle size <3mm, heated to 500-650℃ in a tube furnace under nitrogen atmosphere at a heating rate of 5-10℃ / min, and kept at a constant temperature for 1-3h. After cooling, primary biochar is obtained. The primary biochar is mixed with an ammonia solution with a mass fraction of 10%-25% at a solid-liquid ratio of 1:5-1:10, and impregnated at 60-80℃ for 4-8h. The mixture is filtered and washed until the pH of the filtrate is 8-9, dried at 80-100℃ until the water content is <5%, and crushed through a 40-120 mesh sieve to obtain alkaline functional group modified biochar. Step 4, Preparation of amino acid chelated trace elements: Zinc sulfate, ferrous sulfate, manganese sulfate, and boric acid are mixed and dissolved in deionized water at a mass ratio of 1:2:0.6:0.4 to prepare a mixed trace element solution with a total concentration of 50-100 g / L. Amino acids are added to make the molar ratio of amino acids to metal ions 2:1-3:

1. The pH value is adjusted to 6-7. The mixture is stirred and chelated at 60-70℃ for 2-4 hours. After cooling, it is spray-dried to obtain amino acid chelated trace element powder. Step 5, Preparation of the compound functional bacterial agent: Inoculate *Bacillus pasteurellii*, salt-tolerant phosphate-solubilizing bacteria, and salt-tolerant nitrogen-fixing bacteria into their respective liquid culture media. Incubate at 30-35℃ with shaking at 150-200 rpm for 24-48 hours until the logarithmic growth phase. Collect the bacterial cells by centrifugation, resuspend in sterile physiological saline, and mix the three bacterial solutions at a volume ratio of 2:1:

1. Add sodium alginate as a protectant, and spray-dry or freeze-dry to prepare the bacterial powder. The total viable count is... pcs / g; Step 6, Preparation of polyglutamic acid-encapsulated sustained-release urea: Urea particles and γ-polyglutamic acid aqueous solution are spray-coated in a fluidized bed coating machine at a mass ratio of 1:0.1-1:0.

3. The spray temperature is controlled at 50-70℃, the spray pressure is 0.1-0.3MPa, and the coating time is 30-60min, resulting in sustained-release urea particles coated with a polyglutamic acid film. These particles are then dried at 60℃ until the moisture content is <2%. Step 7, Mixing and Granulation: Weigh out the alkali-fused activated steel slag powder, hydrothermally modified neutralized red mud, alkaline functional group modified biochar, amino acid chelated trace elements, and polyglutamic acid-encapsulated slow-release urea according to the formula ratio. Mix them in a high-speed mixer for 5-10 minutes. Add the compound functional bacterial agent and mix evenly. Dissolve sodium carboxymethyl cellulose in deionized water to prepare a binder solution with a mass fraction of 2%-5%. Granulate the material while spraying the binder solution in a disc granulator, controlling the material moisture content to 15%-25% and the granulation time to 15-30 minutes to obtain wet granules with a particle size of 2-5 mm. Dry the wet granules in a low-temperature fluidized bed dryer at 40-50℃ until the moisture content is <10%. Screen the finished granules to obtain a particle size of 2-4 mm, and package and seal them for storage.

7. The preparation method according to claim 6, characterized in that, In step one, the sodium hydroxide solution used for the alkaline fusion activation reaction has a mass fraction of 25%–35%, a solid-liquid ratio of 1:2.5–1:3.5, a reaction temperature of 130–150℃, and a reaction time of 3–4 hours.

8. The preparation method according to claim 6, characterized in that, In step two, the sulfuric acid solution used for neutralization reaction has a mass fraction of 12%–18%, a solid-liquid ratio of 1:4–1:5, a hydrothermal treatment temperature of 160–180℃, and a hydrothermal treatment time of 3–5 hours.

9. The preparation method according to claim 6, characterized in that, In step three, the pyrolysis temperature is 550-620℃, the pyrolysis time is 1.5-2.5h, the ammonia concentration for ammonia modification is 15%-20%, the solid-liquid ratio is 1:6-1:8, the modification temperature is 65-75℃, and the modification time is 5-7h.

10. The preparation method according to claim 6, characterized in that, In step seven, the material moisture content is 18%–22%, the granulation time is 20–25 min, and the drying temperature is 42–48℃.

Citation Information

Patent Citations

  • Saline alkali soil conditioner and method for preparing saline alkali soil conditioner from phosphate rock tailings and low-rank coal

    CN111303896A

Cited By

  • Harmless treatment method for rare earth smelting waste residues

    CN119259664A